Strategi efektif pendidikan anti korupsi dalam membentuk karakter integritas di sekolah dan perguruan tinggi - Nurjanatin, Ririt (Maliki Interdisciplinary Journal, 2026)
Corruption in Indonesia is a systemic problem that threatens the nation’s integrity and identity, thus requiring preventive efforts through Anti-Corruption Education (ACE). This study aims to examine effective strategies for internalizing integrity values in schools and universities using a literature review method. The findings indicate that the effectiveness of ACE depends on a comprehensive approach, including curriculum reorientation that balances cognitive and affective aspects, educator role modeling, and strengthening a clean academic culture through the hidden curriculum. In addition, experiential and participatory learning methods such as honesty canteens and social audits help reinforce students’ direct practice of integrity values. However, the implementation of ACE still faces challenges such as environmental resistance and inconsistency of values outside educational institutions. Therefore, stronger regulations, the use of technology, and collaboration among schools, families, and society are necessary. With consistent implementation, ACE is expected to develop a generation with strong integrity and contribute to national resilience and sustainable development. Thus, Anti-Corruption Education is not only an educational instrument, but also a fundamental strategy in building the character of a generation with integrity, so that it is able to realize clean, fair, and sustainable national governance.